Surviving Vegas, a buck at a time (Area 51 Film Group, LLC, 2014)
Surviving Vegas: A Buck At A Time is a documentary motion picture that follows street performers in Las Vegas, Nevada; specifically, focusing on people who dress up as various characters. The crazy and bizarre characters solicit tourists for tips in exchange for taking photos with them. --